The Meaning of Jilbāb and Khimār in Contextual Interpretation: Integrating Gadamer's Hermeneutics and Ulūm al-Qur'ān - Zaman, M. Badruz; Rakhman, Itmam Aulia; Mundzir, Ahmad (QOF, 2024)
This article explores the contextual meaning of jilbāb and khimār in the Qur’an by integrating Hans-Georg Gadamer’s hermeneutics and the classical framework of ‘ulūm al-Qur’ān (the sciences of Qur’anic interpretation). The study addresses the central problem of how verses on jilbāb (Q.S. al-Aḥzāb [33]: 59) and khimār (Q.S. an-Nūr [24]: 31) can be interpreted through the fusion of horizons between text and reader, especially in light of contemporary gender and modesty discourses. Using descriptive-analytical library research, this article draws from primary sources—the Qur’an and Gadamer’s philosophical works—alongside secondary references on tafsir and hermeneutics. The findings reveal that jilbāb and khimār are best understood as protective-preventive measures rooted in both historical context and ethical intentions. Rather than prescribing fixed models of clothing, the Qur’anic injunctions emphasize dignity, modesty, and the social protection of women. By applying Gadamer’s key concepts—effective history (Wirkungsgeschichte), pre-understanding (Vorverständnis), and fusion of horizons (Horizontverschmelzung)—the study demonstrates how traditional interpretations may evolve through dialog with present-day realities. This approach contributes to the ongoing discourse on gender, religious norms, and the role of interpretation in Islamic scholarship.